NiO-CNT composite for high performance supercapacitor electrode and oxygen evolution reaction. (1st September 2018) - Roy, Atanu; Ray, Apurba; Saha, Samik; Ghosh, Monalisa; Das, Trisha; Satpati, Biswarup; Nandi, Mahasweta; Das, Sachindranath
Abstract: Nickel-oxide-Carbon nanotube (NiO-CNT) composite has been synthesized and its multifunctional electrochemical properties have been demonstrated by investigating the supercapacitive performance and the oxygen evolution reactivity. The composite exhibits interlinked porous structure and offers high surface area which has been observed by X-ray diffraction, Field emission scanning electron microscopy, Transmission electron microscopy and Brunauer-Emmett-Teller surface area analysis. NiO-CNT composite offers a specific capacitance of 878.19 F g −1 at a scan rate of 2 mV s −1 along with high cyclic stability. Asymmetric supercapacitor has been fabricated with the composite material as positive electrode and activated carbon as negative electrode and 1 M Na2 SO4 electrolyte medium. The device offers a specific capacitance of 197.7 F g −1 at a scan rate of 2 mV s −1 . It exhibits specific energy and specific power 85.7 Wh kg −1 and 11.2 kW kg −1, respectively. The device is capable of powering LED and DC motor for several minutes. Moreover, NiO-CNT composite shows excellent activity as a catalyst for Oxygen Evolution Reaction. The composite offers an overpotential of 0.301 V. The material shows excellent long term performance. This multifunctional composite material is a promising candidate for future applications in energy storage and conversion.